2016
DOI: 10.18632/oncotarget.8903
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum neurotoxin type C protease induces apoptosis in differentiated human neuroblastoma cells

Abstract: Neuroblastomas constitute a major cause of cancer-related deaths in young children. In recent years, a number of translation-inhibiting enzymes have been evaluated for killing neuroblastoma cells. Here we investigated the potential vulnerability of human neuroblastoma cells to protease activity derived from botulinum neurotoxin type C. We show that following retinoic acid treatment, human neuroblastoma cells, SiMa and SH-SY5Y, acquire a neuronal phenotype evidenced by axonal growth and expression of neuronal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…We were surprised to find that BoNT/C mutants exert different neurodegenerative effects in cultured neurons. This effect was previously attributed to cleavage of SNAP-25 and syntaxin-1A/1B, and to the complete elimination of one of them [ 40 , 41 ]. However, we found that in vitro neurodegeneration triggered by BoNT/C-wt and BoNT/C α-51 occurs even if a small portion of syntaxin-1A/1B is resistant to cleavage.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We were surprised to find that BoNT/C mutants exert different neurodegenerative effects in cultured neurons. This effect was previously attributed to cleavage of SNAP-25 and syntaxin-1A/1B, and to the complete elimination of one of them [ 40 , 41 ]. However, we found that in vitro neurodegeneration triggered by BoNT/C-wt and BoNT/C α-51 occurs even if a small portion of syntaxin-1A/1B is resistant to cleavage.…”
Section: Discussionmentioning
confidence: 93%
“…BoNT/C is long known to cause neurodegeneration in neuronal cultures [ 39 41 ], and this effect can be monitored by staining neurofilament-200 (NF200), a major component of axon cytoskeleton. After 12 hours of incubation, BoNT/C-wt caused a substantial loss of NF200 and the formation of varicosities, also filled with cleaved SNAP-25, all along the neurites ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1B shows that no cleavage was detected when the cells were incubated with concentrations as high as 30 nM BoNT/B. However, when BoNT/B entry was facilitated by Lipofectamine 3000 ( Rust et al, 2016 ), we observed dose-dependent disappearance of VAMP2, indicating that BoNT/B can cleave VAMP2 but is unable to enter N2A cells. Following BoNT/B-induced cleavage there were no VAMP2 breakdown products ( Figure 1C ) most likely due to their immediate degradation by intracellular clearance mechanisms ( Foran et al, 2003b ).…”
Section: Resultsmentioning
confidence: 91%
“…In three studies, investigators injected BoNT into a malignant tumor and demonstrated cellular apoptosis and reduction of tumor size [57][58][59] (Table 3). In another six studies, adding BoNT-A to cancer cell cultures reduced cell growth, induced apoptosis, and inhibited mitosis in various cancer cell lines: Prostate, breast, colon, and pancreatic tumors [60][61][62][63][64][65]. In one study, transfection of insulin secreting cells by BoNT-A reduced insulin secretion, suggesting a potential for treatment of insulinomas [66].…”
Section: The Effects Of Botulinum Neurotoxins Injections On Malignantmentioning
confidence: 99%